Estudo genético quantitativo da qualidade da carcaça e da carne e suas associações com as características de avaliação visual na raça Nelore - Gordo, Daniel Gustavo Mansan [UNESP] (2014)
Brazil is the largest beef exporter and the second beef producer in the world. However, the Brazilian cattle composite is mostly Bos indicus, which produces meat with less quality than Bos taurus. Despite the importance of carcass (CARC) and meat quality (MQ) traits for the beef production cycle, its selection is not applied. Genetic evaluation after harvest is expensive because it requires a long period of time for the trait to be evaluated and consequently, also requires a progeny test. Therefore, the indirect selection through the traits which are commonly applied on breeding programs is feasible. Within this context, the visual evaluation using scores has been used on breeding programs, aiming to improve the carcass traits. The objective of the present study was to evaluate the genetic parameters of CARC and MQ, as well as their genetic associations with visual scores in Nellore cattle. For CARC and MQ traits were used only males, from animals that were born between 2008 and 2010, raised on grazing system and kept around 90 days in feed lot system for finishing. Records of 36,600, 36,550, 36,550, 1,442, 1,441, 1,435, 1,533, 1,535, 1,535, 1,534, 1,533 and 1,522 for yearling conformation (C), yearling finishing precocity (P), yearling muscling (M), rib eye area (REA), hot carcass weight (HCW), fat thickness (FT), Warner - Bratzler shear force (SF), marbling score (MS), lightness (L*), redness (a*), yellowness (b*) and intramuscular lipid (IL), respectively, were used. The (co)variance components were estimated by the restricted maximum likelihood method using tri and multitrait animal model. For the visual scores the model included the genetic additive and residual random effects, the contemporary group (CG) as a fixed effect and age of the animal (linear and quadratic) as covariate. For CARC and MQ the model included the genetic additive effect and residual effect as random effects, and ...